2020
DOI: 10.1016/j.onehlt.2020.100181
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and control of COVID-19 in pastoral community through One Health Approach

Abstract: The vast majority of its population being a pastoralist community, the Somali region in Ethiopia shares the longest border with its neighboring east African countries. These communities face a high risk for transmission of imported COVID-19 cases and remain vulnerable due to lack of access to health delivery and low utilisation of services. Valuable lessons from other countries, has placed the One Health Approach as an appropriate, feasible and applicable preventive and control measure for COVID-19. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The complex and interconnected determinants of food security among African pastoralists, including access and utilization of health services, access to markets, droughts and environmental variation, conflict, and more recently the COVID-19 pandemic, cannot be addressed by one sector or group of stakeholders. It instead requires a One Health approach in which intersectoral collaboration across groups of stakeholders generates broad solutions that combat the combined impacts of the pandemic and other livelihood shocks (Egeru et al, 2020;Griffith et al, 2020b;Yousuf et al, 2020). As it relates to the pandemic, One Health provides the opportunity to implement targeted public health measures in combination with livelihood support, overall resulting in improved food security (Food Security Cluster, 2020;Griffith et al, 2020b;Mardones et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The complex and interconnected determinants of food security among African pastoralists, including access and utilization of health services, access to markets, droughts and environmental variation, conflict, and more recently the COVID-19 pandemic, cannot be addressed by one sector or group of stakeholders. It instead requires a One Health approach in which intersectoral collaboration across groups of stakeholders generates broad solutions that combat the combined impacts of the pandemic and other livelihood shocks (Egeru et al, 2020;Griffith et al, 2020b;Yousuf et al, 2020). As it relates to the pandemic, One Health provides the opportunity to implement targeted public health measures in combination with livelihood support, overall resulting in improved food security (Food Security Cluster, 2020;Griffith et al, 2020b;Mardones et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while herders may work alone for days, they are more often working with partners who are likely to change along with the seasonal regrouping of the herd (Paine, 1994 :103). Herders from different groups must occasionally work together to separate herds that are mixed or retrieve animals that have wandered off (Paine, 1994 :103). Thus, social distancing and infection control measures might impact day-to-day work conditions for reindeer herders.…”
Section: The Status Of Covid-19 In the Reindeer Husbandry In Norwaymentioning
confidence: 99%
“…Restricting mobility and social distancing have proven to be effective measure to control the spread of COVID-19 (Kissler et al, 2020 ). Nomadic pastoralists, who are highly mobile for daily herding of their livestock, are thus at higher risk of a rapid spread of COVID-19 (Egeru et al, 2020 ; Griffith et al, 2020 ; Yousuf et al, 2020 ) so that the management of the pandemic amongst pastoralists is especially challenging (Griffith et al, 2020 ). For example, among pastoralists in the Greater Horn of Africa, Griffith et al ( 2020 ) found that COVID-19 control efforts negatively impact livelihoods and food, income, and nutrition security.…”
Section: Introductionmentioning
confidence: 99%